Fatal septicemia caused by Chromobacterium violaceum in a child from Colombia Septicemia mortal causada por Chromobacterium violaceum en una paciente pediátrica de Colombia - Pedro Martinez; Salim Mattar (Revista do Instituto de Medicina Tropical de São Paulo, 2007)
A 4-year old child living in Colombia presented with a history of fever and severe abdominal pain for four days. The patient developed pneumonia, septic shock, multiple organ failure and died on the fifth day of hospitalization. Chromobacterium violaceum was isolated from admission blood cultures and was resistant to ampicillin, cephalosporins, carbapenems and aminoglycosides. Una niña de 4 años que vivía en Colombia presentó historia de fiebre y dolor abdominal severo por cuatro días. La paciente desarrollo neumonía, shock séptico, múltiple falla de órganos y muerte el quinto día de hospitalización. Chromobacterium violaceum fue aislado de cultivos de sangre y mostró resistencia a ampicilina, cefalosporinas, carbapenems y aminoglicosidos.